2018
DOI: 10.1038/s41467-018-07163-4
|View full text |Cite
|
Sign up to set email alerts
|

Src-transformed cells hijack mitosis to extrude from the epithelium

Abstract: At the initial stage of carcinogenesis single mutated cells appear within an epithelium. Mammalian in vitro experiments show that potentially cancerous cells undergo live apical extrusion from normal monolayers. However, the mechanism underlying this process in vivo remains poorly understood. Mosaic expression of the oncogene vSrc in a simple epithelium of the early zebrafish embryo results in extrusion of transformed cells. Here we find that during extrusion components of the cytokinetic ring are recruited to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 69 publications
3
20
0
Order By: Relevance
“…This is consistent with reports that membranous PA directly binds cytoplasmic Sphk1, thereby recruiting it to cell membrane compartments (Delon et al, 2004). Plasma membrane localization of Sphk1 in turn would allow the release of S1P into the extracellular space, where it could act in an autocrine and/or paracrine manner to facilitate cell extrusion, in agreement with previous reports of extruding vSrc-transformed cells (Anton et al, 2018).…”
Section: Matriptase As a Tumor Suppressorsupporting
confidence: 93%
“…This is consistent with reports that membranous PA directly binds cytoplasmic Sphk1, thereby recruiting it to cell membrane compartments (Delon et al, 2004). Plasma membrane localization of Sphk1 in turn would allow the release of S1P into the extracellular space, where it could act in an autocrine and/or paracrine manner to facilitate cell extrusion, in agreement with previous reports of extruding vSrc-transformed cells (Anton et al, 2018).…”
Section: Matriptase As a Tumor Suppressorsupporting
confidence: 93%
“…While BCE is reminiscent of cytokinesis, Fig. 4h and other images show the nucleus remains beneath the contractile ring, disfavouring asymmetric cell division as an invasion mechanism, seen in Src-expressing cells 34 .…”
Section: Resultsmentioning
confidence: 90%
“…A related phenomenon was also observed in a zebrafish model of pancreatic tumour initiation, in which labelling tumour-initiating cells with a marker of differentiation revealed that oncogene expression blocked differentiation, leading to tumourigenesis [26]. Interestingly, live imaging has also led to the observation that cells expressing oncogenic Ras or v-Src can be extruded from the epidermis by healthy neighbouring cells, indicative of a potential tumour-suppressive defence mechanism [32][33][34].The main limitation in the use of transgenic models to study tumour initiation is that oncogene expression is dependent upon tissue-specific promoters, for which timing of activation can vary. This also restricts the study of early events to larval zebrafish.…”
mentioning
confidence: 76%